Comparative Study of Hypovitaminosis B12 Associated with Metformin in Combination with Sulfonylurea or Dpp-4 Inhibitors - Aseem, Syed; Ruman, Shehzad; Tabassum, Sheema; Tabasum, Shaheestha; Fatima, Samreen; Begum, Safa; Malik, Shoeb (Indian Journal of Pharmacy Practice)
Introduction: The purpose of this study was to estimate the prevalence of hypovitaminosis B12 effect of metformin and its combination with sulfonylureas or DPP-4 inhibitors for type-2 diabetes mellitus patients. Retrospective chart analysis was done for patients seen by a provider between January 1 and December 31, 2019. Materials and Methods: The study was conducted at Shadan Teaching hospital and research centre, Peerancheru, Hyderabad, Telangana. The study period was six months which started from September 2022. 150 patients were enrolled in study based on inclusion and exclusion criteria. This data was analysed using ANOVA [one way Analysis] and the results were computed. Results: The main result was the frequency of monitoring for vitamin B12 within a year. The prevalence of normal (>350 pg/mL) levels and deficient (200 pg) levels was compared. Correlation of vitamin B12 levels and the parameters such as age, gender, duration of T2DM and diabetic neuropathy was done and represented graphically. Low, Borderline and Normal levels of vitamin B12 were determined with respect to the grades of diabetic neuropathy. Conclusion: According to our findings, the patients who are on metformin therapy singly had a greater prevalence of Vitamin B12 deficiency. In comparison to patients receiving Metformin and DPP-4 Inhibitors, those receiving Metformin and Sulfonylureas combination therapy had a comparatively greater rate of Vitamin B12 deficiency. The severity of diabetic neuropathy, a low Vitamin B12 diet, poor medication adherence and hyperglycaemia all contributed to the inference of severe vitamin B12.
Keywords: B12 Deficiency; Diabetic Neuropathy; OHA combinations; Prevalence